The Prognosis of Leptin rs2167270 G > A (G19A) Polymorphism in the Risk of Cancer: A Meta-Analysis - Zhang, Aiqiao; Wang, Shangren; Zhang, Fujun; Li, Wei; Li, Qian; Liu, Xiaoqiang (Frontiers in Oncology, 2021)
Abstract Background: Although the effect of the LEP G19A (rs2167270) polymorphism on cancers is assumed, the results of its influence have been contradictory. A meta-analysis was conducted to precisely verify the relationships between LEP G19A and the development of digestion-related cancers. Methods: Investigators systematically searched the literature in PubMed, Embase and Web of Science and used STATA software 14.0 for the meta‑analysis. The odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate the associations. Subgroup analyses stratified by ethnicity, cancer type and cancer system were further conducted to assess the relationship between the LEP G19A polymorphism and digestion-related cancers. Results: In the overall population, we found a significant relationship with overall cancer (allele comparison: OR=0.921, p=0.000; dominant comparison: OR=0.923, p=0.004; recessive comparison: OR=0.842, p=0.000; homozygote model: OR=0.0843, p=0.001). In a subgroup analysis conducted by ethnicity, we obtained significant results in Asians (Asians allele comparison: OR=0.885, p=0.000; dominant comparison: OR=0.862, p=0.000; homozygote model: OR=0.824, p=0.039; and heterozygote comparison: OR=0.868, p=0.000) but not in Caucasians. In a subgroup analysis conducted by cancer type and cancer system, we obtained significant results that the LEP G19A polymorphism may decrease the risk of colorectal cancer, esophageal cancer, digestive system cancer and urinary system cancer Conclusions: This meta-analysis revealed that the LEP G19A polymorphism may decrease the risk of cancer.